POLEMIC OF THE CRIMINAL CODE BILL FROM THE PERSPECTIVE OF ADVOCATES - Soekasah, Siti Sakina (Awang Long Law Review, 2023)
Indonesia's existing Criminal Code (KUHP), a remnant from the Dutch East Indies colonial era, is regarded as outdated and disconnected from current societal realities. This has spurred the Indonesian Government to initiate a comprehensive update of the criminal provisions via the Draft Criminal Code (RUU KUHP), which has been in the making for several decades. The RUU KUHP aims to accommodate the evolving needs of the nation's criminal law system. However, this endeavour has sparked controversy, particularly regarding Articles 282 and 515 of the RUU KUHP, which are viewed as discrediting Advocates as independent enforcers of the law. These articles are claimed to be at odds with the Advocate Act, the lex specialis of the RUU KUHP, raising concerns about the potential impact on the professional status of Advocates. Moreover, Article 281 of the RUU KUHP has raised alarms due to its potential as a 'rubber article', susceptible to multiple interpretations, which could undermine the principle of legal certainty. This normative-juridical study utilises a descriptive-analytical methodology to analyse these contentious aspects of the RUU KUHP. It concludes that the provisions regarding Advocates conflict with the Advocate Act, and the ambiguity in Article 281 raise the risk of misuse and legal uncertainty. While the RUU KUHP signifies a crucial effort towards modernising the nation's criminal law system, these issues must be addressed to ensure its credibility and effectiveness.